Estimates of quantum bounds pertaining to new q-integral identity with applications - Awan, Muhammad Uzair; Talib, Sadia; Kashuri, Artion; Noor, Muhammad Aslam; Chu, Yu-Ming (Advances in difference equations, 2020)
In this article, we establish a new generalized q -integral identity involving a q -differentiable function. Using this new auxiliary result, we obtain some new associated quantum bounds essentially using the class of preinvex functions. At the end, we present some applications to the special bivariate means to show the significance of the obtained results. Our approaches and obtained results may lead to further applications in physics.